2022
DOI: 10.1038/s41598-022-09350-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel probiotic treatment of autism spectrum disorder associated social behavioral symptoms in two rodent models

Abstract: The prevalence of autism spectrum disorder (ASD) has rapidly increased in the past decades, and several studies report about the escalating use of antibiotics and the consequent disruption of the gastrointestinal microbiome leading to the development of neurobehavioral symptoms resembling to those of ASD. The primary purpose of this study was to investigate whether depletion of the gastrointestinal microbiome via antibiotics treatment could induce ASD-like behavioral symptoms in adulthood. To reliably evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 92 publications
2
14
0
Order By: Relevance
“…Although animal studies showed that probiotic supplementation improved ASD-like symptoms and social behavior in mice [ 38 , 39 ], in our meta-analysis, the pooled SMD (−0.24, 95% CI: −0.60 to 0.11, p = 0.18) showed that probiotic supplementation did not improve the associated behavioral symptoms in children with ASD, which is consistent with previous findings [ 37 , 40 ]. The pooled SMD in each subgroup by country, scale, and duration of intervention also showed the same results.…”
Section: Discussionsupporting
confidence: 92%
“…Although animal studies showed that probiotic supplementation improved ASD-like symptoms and social behavior in mice [ 38 , 39 ], in our meta-analysis, the pooled SMD (−0.24, 95% CI: −0.60 to 0.11, p = 0.18) showed that probiotic supplementation did not improve the associated behavioral symptoms in children with ASD, which is consistent with previous findings [ 37 , 40 ]. The pooled SMD in each subgroup by country, scale, and duration of intervention also showed the same results.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, prenatal exposure to maternal immune activation (MIA) is considered a key environmental risk factor for ASD (Han et al, 2021 ; Mirabella et al, 2021 ; Xu et al, 2021 ). Animal models for ASD conducted by prenatal exposure, including prenatal infection, valproic acid, propionic acid, poly (I:C) or lipopolysaccharides exposure, can cause ASD-like behaviors, such as specific impairments in social interaction, communication and repetitive behaviors (Ergaz et al, 2016 ; Mintál et al, 2022 ). The MIA mice model is one of the most frequently studied models of ASD in which a single prenatal exposure to poly (I:C) results in behavioral, neurological, and immunological abnormalities of the offspring (Knuesel et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…β-endorphin, endogenous opioid peptides, may alter social behavior and result in autistic-like features. A probiotic mixture was shown to attenuate both the antibiotics and VPA-induced autistic behavioral symptoms ( Mintál et al, 2022 ). In the BTBR mouse model of autism, probiotic L. rhamnosus administration decreased behavioral abnormalities in social novelty preference and increased 5-aminovaleric acid and choline levels in serum and the PFC, respectively ( Pochakom et al, 2022 ).…”
Section: Probiotics Improve Asd By Regulating Gut–brain Axismentioning
confidence: 99%